A 17-years-old girl presenting with spontaneous cerebrospinal fluid rhinorrhea diagnosed as aqueductal stenosis: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
A 17-year-old girl presented with chronic headache and spontaneous CSF rhinorrhea. She had no history of head trauma. MRI of her brain showed aqueductal stenosis associated with triventriculomegaly with partially empty sella. Following insertion of ventriculoperitoneal shunt, her headache and CSF rhinorrhea completely recovered. Though very uncommon but aqueductal stenosis should be kept as a differential diagnosis for etiology of chronic CSF rhinorrhea.